EFEKTIVITAS SISTEM PENILAIAN KINERJA APARATUR PADA BIRO ADMINISTRASI UMUM DAN KEUANGAN INSTITUT PEMERINTAHAN DALAM NEGERI - Putra, Bintan Nugraha (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2020)
The title of this research is “EFFECTIVENESS OF APARATURE PERFORMANCE ASSESSMENT SYSTEM IN GENERAL AND FINANCIAL ADMINISTRATION BUREAU GOVERNMENTAL INSTITUTE WITHIN COUNTRY”. The research approach used in this study is the inductive approach. The theory used is DeLone and McLean's theory proposed by Sutan Kayo who divides it into 5 (five) dimensions, namely basic knowledge, technical ability, mental attitude, professionalism, and objectivity. The research design used is a qualitative research with a descriptive approach.The results of this study found that of the six dimensions measuring the effectiveness of an information system only a few have problems, namely the quality of information and net benefits, but can still be implemented. Key words : Effectiveness, Assessment System